Literature Review : Development of Digital Pop-Up Book Learning Media for PPKn Learning Material My Country Indonesia in Elementary Schools - Aisyah (Berpusi Publishing, 2024)
The purpose of this article is to discuss pop-up book learning media used in elementary schools to help students learn. This is a literature review using content analysis techniques. To improve students' reading skills in elementary schools, researchers studied research and other written works that were relevant to the topic of the article in pop-up book learning media. Researchers go through several stages in reviewing previous research, such as selecting relevant research, collecting data and information for study, determining the state of the art of research that has been analyzed, developing the results of information analysis and assembling them into a conclusion. The results of this research can be concluded that the existence of learning media is a very important thing in Civics learning, especially at the elementary school level. It is necessary to utilize learning media to achieve the learning objectives desired by the teacher.